Persepsi antara Risiko Keselamatan Berkendaraan dengan Perilaku Pemakaian Safety Belt pada Driver Truk - Muhamad Bob Anthony (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2018)
Deaths and injuries from traffic accidents have become health problems for people throughout the world including Indonesia. The saddest data from the victims who died due to traffic accidents found that 10,428 people were killed in 2017 because the drivers did not use seat belts. This research aims to see the relationship between the perception of safety risk i.e. the ability, knowledge and environmental factors with the behavior of the use of safety belts in truck drivers in mining companies. This research is a comparative causal research i.e. research that states the relationship of one variable causes other variables. What is affected is the dependent variable, namely the use of safety belt behavior and the influencing variable is the independent variable, namely the perception of the risk of driving safety. Participants are 25 mining company truck drivers. The data obtained is then processed and analyzed using the SPSS version 16. Based on the results of data processing and analysis, it is found that the ability, knowledge and work environment factors have an influence on the safety belt usage behavior.